Factors associated with the access of modern family planning methods in women of age venezuelan immigrants in Peru. ENPOVE 2018 - Segundo-Paredes, Jorge (2020)
Objective. Estimate the prevalence and determine the factors associated with access to modern family planning methods (MPFM) in women of childbearing age Venezuelan immigrants in Peru. Materials and methods. Observational, cross-sectional and analytical study of the Survey Directed to the Venezuelan Population Residing in the Country (ENPOVE) 2018. The proportion of women of fertile age Venezuelan immigrants with access to MPFM was calculated. Crude and adjusted prevalence ratios (RP) of MPFM access were estimated, using generalized linear models. Results. 3,378 Venezuelan immigrant women of childbearing age were included. 78.45% did not have access to MMPF. Being in the young stage of life (RPa: 1.07; IC: 1.05-1.14), being married (RPa: 1.09; IC: 1.03-1.14), living together (RPc: 1.11; IC: 1.06-1.16), residing in the city de Trujillo (RPa: 1.21; CI: 1.13-1.29) were associated with a higher probability of accessing MPFM. Conclusions. Three out of ten women of childbearing age Venezuelan immigrants in Peru have access to MPFM. Being young, married, living together, and residing in the city of Trujillo increases the probability of accessing Venezuelan immigrants to Peru in MMPF. Sexual and reproductive health services should be prioritized to those to cities and life stages with greater barriers in accessing MPFM.